Efficient, long term production of monocyte-derived macrophages from human pluripotent stem cells under partly-defined and fully-defined conditions. - Bonnie van Wilgenburg; Cathy Browne; Jane Vowles; Sally A Cowley (PLoS ONE)
Human macrophages are specialised hosts for HIV-1, dengue virus, Leishmania and Mycobacterium tuberculosis. Yet macrophage research is hampered by lack of appropriate cell models for modelling infection by these human pathogens, because available myeloid cell lines are, by definition, not terminally differentiated like tissue macrophages. We describe here a method for deriving monocytes and macrophages from human Pluripotent Stem Cells which improves on previously published protocols in that it uses entirely defined, feeder- and serum-free culture conditions and produces very consistent, pure, high yields across both human Embryonic Stem Cell (hESC) and multiple human induced Pluripotent Stem Cell (hiPSC) lines over time periods of up to one year. Cumulatively, up to ∼3×10(7) monocytes can be harvested per 6-well plate. The monocytes produced are most closely similar to the major blood monocyte (CD14(+), CD16(low), CD163(+)). Differentiation with M-CSF produces macrophages that are highly phagocytic, HIV-1-infectable, and upon activation produce a pro-inflammatory cytokine profile similar to blood monocyte-derived macrophages. Macrophages are notoriously hard to genetically manipulate, as they recognise foreign nucleic acids; the lentivector system described here overcomes this, as pluripotent stem cells can be relatively simply genetically manipulated for efficient transgene expression in the differentiated cells, surmounting issues of transgene silencing. Overall, the method we describe here is an efficient, effective, scalable system for the reproducible production and genetic modification of human macrophages, facilitating the interrogation of human macrophage biology.